STRUCTURAL RELIABILITY ANALYSIS BASED ON AN IMPROVEMENT OF THE RESPONSE SURFACE METHOD - ZHANG XueGang (Jixie qiangdu)
In order to reduce sample points and make full use of information resources of sample points, an improvement of the response surface method for structural reliability analysis was developed, that structural reliability index was regarded as convergence condition. The method used mixed response surface method during iterations, at the first iteration a linear response surface function was used, at the following iteration a quadratic polynomial response surface without mixed terms was used. Then the sample points near the failure boundary from all sample points were selected after convergence, the limit state function was built by a quadratic polynomial response surface with mixed terms and square terms, and finally the structural reliability was calculated by the Monte Carlo method. Numerical examples show that the response function is able to approximate the real failure curve, and effectively improves the reliability calculation accuracy, using mixed response surface method during iterations sample points are reduced, in other words computing time in engineering are decreased.